An Analytical Study of Ph.D. and M.A. Theses/Dissertations in Education Administration at the Faculty of Education, Yarmouk University (2017-2021) - Alattari , Aref Tawfiq; Alrousan, Salam Mamdouh (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed at analyzing the Ph.D./MA theses/dissertations that were approved at the faculty of education, Yarmouk University, Jordan in the last five years (2017-2021) according to some quantitative indicators such as the kind of thesis, year of publication, sex of authors, mode of supervision, target study population, methodology, and theme. Methods: The authors applied the basic bibliometric methodology. The sample consisted of (149) Ph.D. and MA theses/dissertations. Results: The results revealed that there was a steady increase in the number of theses/dissertations (from 22 in 2017 to 44 in 2020). The number of doctoral theses was almost three times that of MA dissertations (73.% to 26.17%, respectively); female authors outnumbered males; the prevalent mode of supervision is the single-supervision mode; the focus was on public education and higher education; the quantitative methodology was used in the vast majority of them; and the interest was on applying leadership theories, identifying leadership styles, and investigating roles and functions of administrators. Conclusions: This research recommends diversifying the research methodologies used and conducting further systematic reviews of educational administration scholarships in Jordan.